Histiocytoid Melanoma. (June 2020) - Harvey, Nathan T.; Grewal, Jagbir; Ardakani, Nima Mesbah; Robinson, Cleo; Leecy, Tamazin N.; Forrest, Cindy; Texler, Michael; Kattampallil, Joseph; Lam, Minh; Wallace, Corrine; Lum, Dennis; Wood, Benjamin A.
Abstract : Abstract: While most melanomas display well-characterised and readily recognised architectural and cytomorphological features, unusual variants can create diagnostic difficulties. Variants which mimic benign or reactive processes are particularly problematic. We report 5 cases of melanoma characterised by a subtle microscopic appearance reminiscent of a benign dermal histiocytic infiltrate, which we refer to as "histiocytoid melanoma." These lesions are characterised clinically by ill-defined areas of cutaneous pigmentation, which in several cases reached large proportions. Microscopically, there is a subtle interstitial pattern of infiltration by predominantly single cells with a histiocytoid morphology, often resembling melanophages. Immunohistochemical confirmation was typically required, with the cells showing positive labelling for Sox-10 as well as Melan-A. In several examples, the proliferation extended to clinically uninvolved surgical margins, necessitating multiple excisions, and many of our patients have experienced locoregional recurrence. However, none have developed distant metastases or died of melanoma. While uncommon, this subtle variant is important to recognise in order to ensure adequate histological clearance is obtained.